Kesetaraan Uji Mastitis IPB-1 dengan Metode Breed untuk Mendiagnosis Mastitis Subklinis pada Susu Kerbau Murrah dan Kambing (THE EQUALITY OF IPB-1 MASTITIS TEST WITH BREED METHOD FOR SUB-CLINICAL MASTITIS DETECTION ON MURRAH BUFFALO’S MILK AND GOAT’S MILK - Sudarwanto, Mirnawati Bachrum; Maheshwari, Hera; Tanjung, Faisal (Jurnal Veteriner, 2017)
Sub-clinical mastitis causes decrease in milk production and milk quality. It is not only happen tomilking dairies, but also happens to dairy buffalos and goats. The objective of this study is to know thedifferences between IPB-1 mastitis test (IMT) and Breed method to diagnose sub-clinical mastitis ondairy buffaloes and goats. Fourty two samples of buffalo’s milk and 20 samples of goat’s milk were used tosomatic cell count (SCC) with direct and indirect method. Direct method was performed by counting themilk’s SCC with Breed method, and indirect method was performed by observing the reaction betweenIMT reagent and milk. The results showed that 28 from 42 samples (66.67%) of buffalo’s milk and 13 from20 samples (65%) of goat’s milk tested with Breed method came from the herds which suffered from subclinicalmastitis and 27 from 42 samples (64.28%) and 10 from 20 samples (50%) of goat’s milk testedwith IMT showed positive reaction. This research also showed that IMT has sensitivity of 96% and specivicityof 100% for buffalo’s milk and sensitivity of 71% and specivicity of 100% for goat’s milk. IMT can be usedto obtain fast result for sub-clinical mastitis diagnosis and it is faster and easier for buffalo’s and goat’smilk.
Keywords: Sub-clinial mastitis; Breed method; IPB-1 mastitis test (IMT); goat’s milk; murrah buffalo’s milk